Inovasi Media Pembelajaran IPA “Struktur dan Fungsi Bagian Tumbuhan” Menggunakan Kahoot Sebagai Kuis Interaktif untuk Kelas 4 SD - Ayu Novirianti; Ika Putra Viratama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of information technology requires innovative learning media to improve the quality of instruction in elementary schools. One technology-based learning medium that can be utilized is Kahoot as an interactive quiz. This study aims to describe the implementation of Kahoot in science learning on the topic of plant structure and functions and its effects on students’ conceptual understanding, learning activeness, and motivation in fourth-grade elementary school students. This research employed a descriptive approach with data collection techniques including observation, learning outcome tests, and documentation. The results indicate that the use of Kahoot creates a more interactive and engaging learning environment, increases students’ active participation, and enhances their understanding of plant structure and function concepts. In addition, Kahoot is effective as an evaluation tool because it provides immediate feedback and presents learning outcomes quickly and systematically. However, the use of Kahoot also has limitations, particularly its dependence on the availability of digital devices and stable internet access. Therefore, Kahoot can be used as an innovative alternative learning medium, provided that school conditions are considered and it is combined with other learning methods to optimize science learning.